Call centre concepts in libraries : with emphasis on National Library Board, Singapore. - Chua, Jeanne Jia Hui. (2008)
The centralisation of telephone information services in the style of a call centre concept is one of the methods taken by libraries to cut costs. This thesis aims to examine how call centre concepts can be applied in LIS.